Synthesis and Investigation of the Structure and Optical Properties of Nano -Ni-Cr Films - Awadh, Jinan H. (Iraqi Journal of Science, 2020)
The thermal evaporation technique was used to prepare the Ni-Cr films with a thickness of 200 nm and a rate of deposition of 0.22nm/Sec. The annealing was performed at 373 and 473 K. The structural and optical analyses of the grown layers were achieved and XRD patterns showed amorphous structure transferred to polycrystalline for film annealed at 373 and 473 K. AFM analysis showed that the surface of Ni-Cr films is homogenous and the average roughness, optical energy gap and absorption coefficient were increased with increasing annealing temperature (Ta).